2014
DOI: 10.1086/674028
|View full text |Cite
|
Sign up to set email alerts
|

Why Farmers Sometimes Love Risks: Evidence from India

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to Economic Development and Cultural Change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To set risk aversion and discount rate, we first normalized the distribution of agricultural net income. Then, as risk aversion and discount rate correlate with household income (Bauer et al, 2012;Just & Lybbert, 2009;Maertens et al, 2014), we rescaled the normalized income distribution with the mean and standard deviation of the (marginal) risk aversion 𝜎 (0.02, 0.82; Just & Lybbert, 2009) and discount rate r 0.159, 0.193;Bauer et al2012) of Indian farmers. Noise was added to both to prevent that each present-biased agent is also risk taking by definition.…”
Section: Risk Aversion and Discount Ratementioning
confidence: 99%
See 1 more Smart Citation
“…To set risk aversion and discount rate, we first normalized the distribution of agricultural net income. Then, as risk aversion and discount rate correlate with household income (Bauer et al, 2012;Just & Lybbert, 2009;Maertens et al, 2014), we rescaled the normalized income distribution with the mean and standard deviation of the (marginal) risk aversion 𝜎 (0.02, 0.82; Just & Lybbert, 2009) and discount rate r 0.159, 0.193;Bauer et al2012) of Indian farmers. Noise was added to both to prevent that each present-biased agent is also risk taking by definition.…”
Section: Risk Aversion and Discount Ratementioning
confidence: 99%
“…Interest rates: To account for the variation in access to credit and interest rates among farmers, we assigned each agent an interest rate based on their total landholding size, with smaller farmers receiving higher and larger farmers lower rates (Appendix B.2, Maertens et al, 2014;P. D. Udmale et al, 2015).…”
Section: Risk Aversion and Discount Ratementioning
confidence: 99%
“…In low-income countries, some studies also reported less risk taking (11), but others found no association (24)(25)(26), or even more risk taking. For instance, the poorest Indian farmers were found to be extremely willing to take risks (27). Other studies focused on extreme scarcity, and found an increase in risk taking.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, farmers rather rely on expected profits in good conditions (return on investment) than on taking into account occasional losses. Evidences from India through a study on why farmers sometimes even seem to like taking risks, came partly to similar findings, showing the existence of a relationship between risk-loving behavior and wealth and assets (Maertens et al, 2014). Hence, farmers who are afraid of taking risks try to limit possible losses even if it means reducing the likelihood of gains (i.e.…”
Section: Discussionmentioning
confidence: 85%